STUDY OF INEQUALITY AND ECONOMIC DEVELOPMENT OF DISTRICTS RESULTING FROM EXPANSION CASE STUDY: EAST KALIMANTAN PROVINCE - Alma, Zitni (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2024)
East Kalimantan Province had 14 cities/regencies before being divided into two provinces, the expansion of these regions made East Kalimantan Province now only have 9 cities/regencies where 5 cities/regencies merged into North Kalimantan Province. However, in 2013 the area of West Kutai Regency which is included in East Kalimantan Province was divided into West Kutai Regency and Mahakam Ulu Regency, so that East Kalimantan Province now has 10 cities/regencies. Based on the 2020-2021 average, 6.372% are poor people and the Gini index is 0.331%, this shows that there is still economic inequality in the East Kalimantan Province. This study is intended to determine economic development and development inequality between regions in the expansion area. The study was conducted in East Kalimantan Province using secondary data from 2017-2021. Economic development is analyzed using the Klassen typology and Theil Entropy index in order to show fast-advancing and fast-growing regions, developing regions, developed but slow-growing regions and underdeveloped areas and measure inequality between regions in the districts / cities resulting from expansion in East Kalimantan Province.